'Buying Peace' in Chechnya: Challenges of Post-Conflict Reconstruction in the Public Sector. Issue 3 (December 2013) - Zabyelina, Yuliya G.
Whereas there seems to be a consensus on the importance of social services for the success of peacebuilding efforts, the role of corruption in the public sector remains ambiguous. On the one hand, conventional interpretations of the role of corruption in the aftermath of conflict suggest that corruption impedes a successful war-to-peace transition. On the other hand, corruption may be necessary to the survival of ordinary citizens by reinforcing economic efficiency and helping them to gain access to basic social services. This article studies various aspects of post-conflict reconstruction in Chechnya with a particular focus on corruption in in the public sector. It argues that Moscow's strategy of soothing the insurgency in the North Caucasus with generous financial injections has brought some stability at least in the sense of absence of large-scale violence. Despite these seemingly positive results, sweeping corruption in the public sector is likely to undermine the effectiveness of post-conflict reconstruction and development projects in Chechnya in the long run, in this way increasing the likelihood of post-conflict Chechen society sliding back into public discontent and violence.